Fungsi Amalan Tarekat Naqsyabandiyah Di Kalangan Petani Dusun Pinang Lombang Bawah, Desa Sungai Raja, Kecamatan Na Ix-X, Labuhanbatu Utara - Baharuddin Yusuf Ritonga; Maraimbang (Program Pascasarjana, UIN Alauddin Makassar, 2026)
Sufism and ṭarīqa traditions play a significant role in shaping both the spiritual and social dimensions of Muslim communities, particularly in rural settings. Beyond individual devotion, these practices function as moral frameworks that influence work ethics and social cohesion. However, empirical studies that specifically examine the practical functions of ṭarīqa within local agrarian contexts in Indonesia remain limited. This study aims to analyze the historical development of the Naqshbandi Order, its core spiritual practices, and their functional roles in the daily lives of farmers in Pinang Lombang Bawah Hamlet, North Labuhanbatu. Employing a qualitative case study approach, data were collected through observations, in-depth interviews, and documentation, and analyzed using thematic analysis. The findings show that since its introduction in 1961 by Shaykh Abdul Manan Hasibuan, the Naqshbandi Order has been sustained through practices such as dhikr, suluk, and rabithah. These practices enhance psychological well-being, foster discipline, patience, and sincerity in agricultural work, and strengthen social solidarity. This study offers a novel contribution by demonstrating how ṭarīqa practices function as an integrated system of spiritual and socio-economic resilience in a localized agrarian context.